A simulation approach to study of entropic elasticity properties of polymer chain molecules using atomic scale Monte-Carlo - Гранкин, Михаил Викторович; Каргин, Анатолий Алексеевич; Карпов, Эдуард Григорьевич (Eastern-European Journal of Enterprise Technologies, 2014)
This paper describes atomic scale Monte–Carlo studies of entropic elasticity properties of individual polymer chain molecules. An efficient numerical Monte –Carlo sampling approach is outlined and used to evaluate the entropic contribution to the total elastic force.Theoretic predictions of mechanical properties of polymer molecules, particularly complex bio-molecules (proteins, lipids, etc.), are difficult due to effects of entropic elasticity. Entropic elastic force can be a significant contributor to the free energy F of the polymer chain and can even exceed interatomic potential energy U under external mechanical load. Monte-Carlo based approach allows to achieve atomic resolution for molecular structure in contrast to analytical methods. Specific load-extension curves are obtained numerically for a group of molecules with degenerate potential energy profiles. Results of the atomistic modeling are compared with the limiting continuum model of the same type of polymers. The extent of the linear and nonlinear elastic regimes and dependence on the molecular weight and geometric parameters of the molecules are discussed. A significant divergence with the continuummodel behavior is observed at smaller bond angles for all elongationsof the molecule. Linearity of the entropic force exists in a wide range ofthe elongations, however, molecules with low gyration radii(densely packedpolymers) are linear mostly in extensionor unfolding, while very sparsely packed molecules are linear mostly in thecontraction mode. The achieved result cannot be reproduced withinthe settings of the continuum model and required an application of atomic scale Monte-Carlo approach developed by our group.